Features of the female mentoring in the Russian management system - I. V. Groshev; T. M. Gololobova (Управление)
The article analyses the problems of female mentoring, which has become a priority in recent years. This is justified by numerous data on the percentage of women in the management of companies in many countries, including Russia, and its dynamics over the past 15 years. The article is based on the methodology of an integrated approach and system analysis. The theoretical basis of the article is the publications of Russian and foreign researchers devoted to the problems of the female mentoring peculiarities in the world and Russian economy sectoral spheres. Familiarisation with regulatory documents and government programs, methods of comparative analysis were chosen as research methods. The methods used also included the method of expert assessments, normative and logical methods. The analysis of methods, mechanisms, tools and other aspects of updating the track of female mentoring and its features in the Russian management system is carried out. Based on the generalization of the obtained research results, the main directions of the development of female mentoring in business, state corporations, public organizations, authorities and other spheres of activity are formulated and a structural diagram of the distinctive features of female mentors is presented. The peculiarities of the female style of mentoring and, in particular, role-left mentoring are considered separately. In conclusion, using the example of the Russian federal project “Women: Mentoring School” in the Year of Science and Technology, as well as the crosscutting trend “Women in male professions. Challenges and advantages” the actualization of the stated issues is given. The presented information will allow business representatives and top management of Russian companies to navigate the established directions in the development of women’s mentoring in various areas of the Russian economy, as well as make rational management decisions.